Resolution of the Council of Experts “Results of a multicenter, randomized, double-blind, placebo-controlled study of ARTNEO in patients with stage II–III primary knee osteoarthritis” - A. M. Lila; L. I. Alekseeva; I. B. Belyaeva; I. B. Vinogradova; N. A. Demidova; O. V. Kalyuzhin; I. I. Nesterovich; V. N. Sorotskaya; L. Yu. Shirokova; S. P. Yakupova (Современная ревматология, 2023)
On August 31,2023 in V.A. Nasonova Research Institute of Rheumatology a meeting of the Expert Council was held at which the principal investigators and co-investigators of the ARTNEO-2021 protocol "Multicenter randomized double-blind, placebo-controlled study of ARTNEO in patients with stage II-III primary knee osteoarthritis" was held. A consensus position was developed on the possibility and feasibility of using a combination of undenatured (native) type II collagen, methylsulfonylmethane, boswellic acids, vitamins C and D (ARTNEO complex) in clinical practice. Based on the results of the study, the use of the ARTNEO complex can be recommended as part of a complex therapy for patients with osteoarthritis as a course treatment with total duration up to 6 months. The results of the study can only be interpreted in relation to ARTNEO and cannot be transferred to preparations with a different composition.